STUDI POLA LINGKARAN PERTUMBUHAN OTOLITH PADA IKAN KATUNG (Pristolepis grooti) YANG DI TANGKAP DI HILIR SUNGAI SIAK PROVINSI RIAU - Chahyadi, Ennie; Windarti, Windarti (Fakultas Perikanan dan Kelautan Universitas Riau, 2015)
In the Siak River, Riau, the water quality in the downstream area is relativelybad due to pollutant originated from several sources such as industrial and domesticwastes. The low quality water may negatively affects the growth of fish and it isreflected in the growth pattern in the otolith of fish living in that river. To understandthe growth pattern in the otolith of Pristolepis grooti (Anabantidae) living in that river,a study has been conducted. Totally 25 fishes were captured from the downstream ofthe Siak River. The otolith were then removed and processed following Windarti(2007)and investigated under a binocular microscope to study the growth ring patternin the otolith. The number of dark growth ring was counted. Results shown that 2 to 5dark growth rings, around 0.086 mm thick were present in the otolith of the fish. Thepresence of the dark growth rings in the otolith indicated that the growth of P. grootiin the downstream of the Siak River was hampered and this fact also suggested that thewater quality in the downstream of the Siak River is not sufficient to support the life P.grooti in that area.